Physical and mechanical properties of particleboard made from oil heat-treated rubberwood particles - Mohd Atkhar, Muhamad Suriadi (2019)
Oil heat treatment on wood particles is one of the feasible methods in reducing the rate of water absorption into the wood particles and can improve the stability of wood particle dimensions. The objective of this study was to determine dimension stability and mechanical properties of the particleboard made of oil-treated rubberwood particles. The rubberwood particles were soaked in cooking palm oil and heated in the oven at 200 ° C for 2 hrs. Particleboard were then fabricated using 4 different ratios of untreated (U) and treated particles (T), namely 100U, 70U:30T, 50U:50T and 30U:70T with urea formaldehyde resin as binders. The particleboard produced were tested for physical and mechanical properties based on the Japanese Industrial standard. The results showed that the wood absorption and thickness swelling of the particleboard made from different ratios of oil heat treated particles were reduced. Meanwhile, the mechanical properties did not adversely affect when up to 50% oil heat treated particles were added.